2021
DOI: 10.1186/s12885-021-08790-9
|View full text |Cite|
|
Sign up to set email alerts
|

Butyrophilin-like 9 expression is associated with outcome in lung adenocarcinoma

Abstract: Background Lung adenocarcinoma (LUAD) is the most prevalent non-small cell lung cancer (NSCLC). Patients with LUAD have a poor 5-year survival rate. The use of immune checkpoint inhibitors (ICIs) for the treatment of LUAD has been on the rise in the past decade. This study explored the prognostic role of butyrophilin-like 9 (BTNL9) in LUAD. Methods Gene expression profile of buytrophilins (BTNs) was determined using the GEPIA database. The effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Pathway analysis of hsa-miR-6514-3p revealed that it is related to the drug metabolism pathway. A study also reported that high expression of hsa-miR-6514-3p in lung adenocarcinoma tumors was associated with good prognosis [30]. In addition, our expression analysis revealed that hsa-miR-6514-3p is expressed at low levels in lung cancers.…”
Section: Discussionsupporting
confidence: 67%
“…Pathway analysis of hsa-miR-6514-3p revealed that it is related to the drug metabolism pathway. A study also reported that high expression of hsa-miR-6514-3p in lung adenocarcinoma tumors was associated with good prognosis [30]. In addition, our expression analysis revealed that hsa-miR-6514-3p is expressed at low levels in lung cancers.…”
Section: Discussionsupporting
confidence: 67%
“…We found these genes to be upregulated in HPV+ and cancer organoids ( Figure 3C ). Another highly upregulated gene was found to be Butyrophilin-Like Protein 9 (BTNL9) which has been implicated to be of prognostic significance in various cancer types ( 43 , 44 ). Its potential involvement in the regulation of γδ T cell mediated killing of tumour cells is unknown but deserves further investigation in light of our current findings with HPV-transformed and cancer organoids.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, they proposed that tissue-specific Btnl/BTNL molecules expressed at steady state bind to an “innate” germline-encoded region on the TCR γ chain of tissue-resident γδ T cells, and that this interaction supports the maintenance of signature Vγ subsets of these cells within tissues (e.g., BTNL3/8 and Vγ4 + IEL in the human gut) but also prevents the engagement of the γδ TCR (incorporating both γ chain and δ chain) with cognate, self-encoded, complementarity-determining region 3 (CDR3)-dependent ligands induced upon tissue stress. Thus, in settings of tissue dysregulation, such as cancer, where BTNL expression is often downregulated [ 132 , 134 136 ], resident γδ T cells may then be released to respond to putative CDR3-dependent, stress-induced activating ligands. In support of this model, a Vγ4 + γδ TCR with defined clonal CDR3 reactivity [ 137 ] has recently been demonstrated to recognise both BTNL3 via a germline-encoded region of the γ chain, as well as the endothelial protein C receptor (EPCR) via the CDR3 [ 128 , 130 , 137 ].…”
Section: Clinical Translation: Challenges and Opportunitiesmentioning
confidence: 99%